2015
DOI: 10.1159/000381716
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Second Primary Malignancies in Patients with Neuroendocrine Tumours

Abstract: Background: An association between neuroendocrine tumours (NET) and increased risk of developing second primary malignancies (SPM) has been recognised. Methods: This was a retrospective review of our institutional prospectively maintained database of NET patients. We identified patients who had been diagnosed with both neuroendocrine and any additional malignancies via examination of patient notes. Results: Clinical data for 169 patients were analysed. After exclusion of patients known to have hereditary tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…Germline variants in MUTYH, CHEK2 and BRCA2 , well‐known breast cancer susceptibility genes were also identified in a whole‐genome sequencing study of 102 pancreatic NET patients . Although one recent SEER national database retrospective study showed an increased risk of pancreatic NET in patients with another first primary malignancy including female breast cancer, this was not found in other population studies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germline variants in MUTYH, CHEK2 and BRCA2 , well‐known breast cancer susceptibility genes were also identified in a whole‐genome sequencing study of 102 pancreatic NET patients . Although one recent SEER national database retrospective study showed an increased risk of pancreatic NET in patients with another first primary malignancy including female breast cancer, this was not found in other population studies …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a SEER database retrospective study showed that the incidence of pancreatic NET is higher in patients with a first primary cancer of the pancreas, bladder, thymus and female breast cancer. However, multiple institutional cohort studies have reported a higher incidence of gastrointestinal and genitourinary second primary malignancies in patients with NETs and an Italian national database study of patients with a primary diagnosis of bronchopulmonary NET has shown a higher incidence of thyroid neoplasms in women and a higher incidence of kidney and bladder tumours in men. Importantly, these studies did not show a higher incidence of breast cancer in NET patients.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies would be warranted to elucidate this transformation in SI-nET occurrence. Also, since there is a high rate of synchronous malignancies in the presence of clinical SI-nET (14)(15)(16), the frequency of other malignancies in patients with SI-nET at autopsy was scrutinized.…”
Section: Introductionmentioning
confidence: 99%
“…Bei bis zu 20 % der Patienten mit NET werden syn-und metachrone Neoplasien anderer Entitäten wie gastrointestinale Adenokarzinome oder Mammakarzinome diagnostiziert [14,15]. Zudem ist eine Vielzahl von genetischen Syndromen, etwa das multiple endokrine Neoplasie-Syndrom Typ 1 (MEN1), das von Hippel-Lindau-Syndrom und die Neurofibromatose Typ 1, mit pankreatischen NET assoziiert [13].…”
Section: Introductionunclassified